LANGUAGE ASSESSMENT LITERACY: A SIGNIFICANT SYSTEMATIC REVIEW - Norazida Ibrahim; Muhammad Azhar Zailani; Harris Shah Abd Hamid (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The importance of Language Assessment Literacy (LAL) in education has received considerable attention in recent years due to its crucial impact on learning and teaching. This article seeks to synthesize existing knowledge, identify research gaps, and offer insights into the complex nature of LAL in educational environments. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. A comprehensive collection of LAL studies was obtained by systematically searching academic databases, specifically Scopus and Web of Science (WoS). The review includes peer-reviewed studies from the social sciences, using a systematic search strategy to find relevant articles. Six main themes were identified in the synthesis of final findings from a review of key themes based on a sample size of 35. These themes are as follows: (1) LAL Components; (2) Teachers’ LAL Levels; (3) Knowledge, Perceptions, and Practices of Language Assessment; (4) The Development of LAL Measures; (5) Professional Development and Training Needs in LAL; and (6) LAL Impacts. This literature review offers a comprehensive synthesis of current research on LAL, providing valuable insights for educators, researchers, and policymakers. The findings contribute to the ongoing discussion on effective language assessment practices in diverse educational settings, providing a basis for further exploration and development of LAL.